The complete works - William Shakespeare... (Clarendon Press,Oxford University Press, 1988)
Here are all of Shakespeare's plays and poems in a compact edition that fits nearly onto your bookshelf or comfortably in your lap. And, as if all of the Bard were not enough, this reissue of an Oxford Classic offers something more: editions of the plays in their theatrical versions, as they were originally performed on the Elizabethan stage. This edition also features a brief introduction to each work, as well as an illuminating General Introduction; reconsiders every detail of the text and presentation of Shakespeare's complete works in the light of modern scholarship; re-examines the nature and authority of the early documents, and freshly establishes the canon and chronological order of composition; and modernizes spelling and punctuation to make the works more accessible to modern readers, without ever altering their original language or meter